The effect of differential disgust conditioning and subsequent extinction versus counterconditioning procedures on women's sexual responses to erotic stimuli. (November 2020) - Pawłowska, Aleksandra; Borg, Charmaine; de Jong, Peter J.; Both, Stephanie
Abstract: Recent theoretical accounts point to disgust as an important factor in the development and persistence of sexual dysfunctions. This study tested if (i) contingent disgust experiences can render initially sexually arousing stimuli disgusting, and (ii) such acquired disgust responses could be best neutralized via a CS-only extinction or a counterconditioning procedure. Participants (N = 74) were exposed to a differential conditioning procedure that was followed by either a CS-only extinction or a counterconditioning procedure. Erotic films served as the CS+/CS-. A disgusting film served as the US. During the extinction procedure, the CS+ was no longer followed by the disgusting US. During counterconditioning the CS+ was paired with positive stimuli. After conditioning, the CS + elicited lower genital arousal and was rated as significantly more disgusting, less pleasant, and less sexually arousing than the CS-. These diminished genital and subjective sexual arousal responses to the CS+ were successfully restored after both the extinction and the counterconditioning procedure, whereas conditioned feelings of disgust and behavioral avoidance persisted. There was no evidence for differential effectiveness of either procedure. Thus, sexual responses can be attenuated by learned sex-disgust associations and restored by extinction and counterconditioning procedures, but conditioned feelings of disgust seem more resistant. Highlights: Sex-disgust associations can be learned through classical conditioning. CS-only extinction and counterconditioning similarly reduced learned sexual disgust. Affective and behavioral sex-disgust associations were difficult to restore.